2011
DOI: 10.4236/jsemat.2011.11001
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Material’s Area Affected during a Micro Thermal Analysis Applied to Homogeneous Materials

Abstract: Micro-thermal analysis (µ-TA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The complex geometry of the probe, especially the NThP, impedes the creation of proper analytical description. In this case, an interesting tool for the analysis of processes in the probe-sample system is numerical simulation based on the finite element method (FEM) [43][44][45][46][47]. So far, we have presented the probe-sample FEM model [39,48] which allowed accurate modeling of the basic physical processes occurring during the SThM measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The complex geometry of the probe, especially the NThP, impedes the creation of proper analytical description. In this case, an interesting tool for the analysis of processes in the probe-sample system is numerical simulation based on the finite element method (FEM) [43][44][45][46][47]. So far, we have presented the probe-sample FEM model [39,48] which allowed accurate modeling of the basic physical processes occurring during the SThM measurement.…”
Section: Introductionmentioning
confidence: 99%
“…From the study of several parameters and conditions, the thermal conductivity has been found to be the driving physical parameter in thermal exchanges. [31] So it is quite crucial to obtain a proper values for thermal conductivities of the equivalent wall. Figure 8 shows the schematic view of pipe, anchors, and refractory wall with their respective dimensions for pilot and industrial scale.…”
Section: Wall Designmentioning
confidence: 99%